Model Integrasi Penjadwalan Produksi Batch dan Penjadwalan Perawatan dengan Kendala Due Date - Zahedi .; TMA Ari Samadhi; Suprayogi .; Abdul Hakim Halim (Jurnal Teknik Industri, 2014)
This paper discusses the integration model of batch production and preventive maintenance scheduling on a single machine producing an item to be delivered at a common due date. The machine is a deteriorating machine that requires preventive maintenance to ensure the availability of the machine at a desired service level. Decision variables of the model are the number of preventive maintenances, the schedule, length of production runs, as well as the number of batches, batch sizes and the production schedule of the resulting batches for each production run. The objective function of the model is to minimize the total cost consisting of inventory costs during parts processing, setup cost and cost of preventive maintenance. The results show three important points: First, the sequence of optimal batches always follows the SPT (short processing time). Second, variation of preventive maintenance unit cost does not influence the sequence of batches. Third, the first production run length from production starting time is smaller than the next production run length and this pattern continues until the due date. When in process inventory unit cost is increased, the pattern will continue until a specified cost limit, and beyond the limit the pattern will change to be the opposite pattern.